Survival of T3 Coliphage in Varied Extracellular Environments. I. Viability of the Coliphage During Storage and in Aerosols - Warren, James C. (1969)
The objective of this study was to determine the feasibility of using airborne T3 coliphage as a viral tracer in microbial aerosols. Although T3 coliphage was relatively stable when stored either at temperatures ranging from 21 to 37 C or in the frozen state at -20 C, there was a 2-log loss in infectivity when stored for 72 days at 4 C. Either agitation of stored coliphage suspensions held at 31 C or wide fluctuations in storage temperature produced an increased loss of infectivity. In the airborne state, freshly prepared coliphage and stored coliphage behaved similarly, with survival diminishing as the relative humidity (RH) was lowered. The greatest loss occurred during the first five min following aerosolization. The results showed that only under certain conditions of temperature and relative humidity can T3 coliphage be used as a satisfactory aerosol tracer.